Effects of different microfracture drilling parameters on bone quality: a finite element analysis - Luo, Jiayi; Zou, Zihao; Zou, Qiang; Luo, Siwei; He, Jialin; Ye, Chuan (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundMicrofracture drilling is a surgical technique that involves creating multiple perforations in areas of cartilage defects to recruit stem cells from the bone marrow, thereby promoting cartilage regeneration in the knee joint. Increasing the exposed bone marrow surface area (more holes in the same area) can enhance stem cell outflow. However, when the exposed area is large, it may affect the mechanical strength of the bone at the site of the cartilage defect. The purpose of this study is to use the finite element method to analyze the effects of drilling diameter, hole spacing, and drilling depth during microfracture surgery on the stability of the bone structure at the cartilage defect site.MethodsIn this study, a normal knee joint model was selected for solid modeling, and a model of a femoral medial condyle cartilage defect was constructed. Microfracture holes with different diameters (1.0 mm, 2.0 mm, 3.0 mm), depths (10 mm, 30 mm), and spacings (1.0 mm, 2.0 mm, 3.0 mm) were created in the femoral medial condyle cartilage defect model. Using Ansys software, the knee joint’s loading conditions in the standing position were simulated, and the structural stability of the model was analyzed. The holes in areas of stress concentration were selected for more detailed mechanical analysis.ResultsThe Von Mises stresses for all the drilling parameters did not exceed the yield strength of the bone. Changes in the drilling parameters did not affect the bone structure around the holes. When smaller diameter drilling tools with closer spacing were used, the average maximum Von Mises stress and the average Von Mises stress on the holes were the lowest.ConclusionAlthough the optimal combination of drilling parameters was not determined, this study provides a mechanical reference for the effects of drilling parameters on bone quality. It demonstrates that using smaller diameter drilling tools with closer spacing in areas of the same defect size results in a greater number of holes, with a lesser impact on bone stability. This study provides a mechanical reference for microfracture drilling.